Reproducibility of diurnal variation in sub-maximal swimming - Martin, L.; Thompson, K. (International Journal of Sports Medicine, 2000)
Swimming training is characterised by the use of early morning and evening training sessions. The purpose of the present study was to investigate if the physiological and kinematic responses to swimming a typical training set are affected by time of day. Seven male collegiate swimmers (age 22 +/- 4 years; height 1.8 +/- 0.1 m; mass 82.1 +/- 4.1 kg) completed a standardised 600 m warm up followed by a 10 x 100 m sub-maximal freestyle set twice a day (06:30-08:00 h and 16:30-20:00 h) on three separate days. Swimming speed was controlled precisely throughout (limits of agreement multilied/divided 1.00) using a new pacing device (Aquapacer, Challenge and Response, Inverurie, Scotland). Oral temperature (To), heart rate (HR), minute ventilation (VE), oxygen uptake (VO2), carbon dioxide expired (VCO2), respiratory exchange ratio (RER), capillary blood lactate (Bla), and glucose (BGL) were measured at rest and post exercise. Stroke rate (SR) and HR were measured during the first nine 100 m repetitions while rate of perceived exertion (RPE) was measured immediately after each 100 m. Significant diurnal variation was found at rest in To, HR, and VO2 on all three days and for VE and VCO2 on two of the days (P<0.05). During the training set no diurnal variation was evident in HR and SR responses or repetition times although RPE values were higher in morning trials compared to evening trials on two of the three days (P < 0.05). Post-exercise significant diurnal variation was found for To and blood glucose for two of the three days (P < 0.05). Therefore, although diurnal variation is evident at rest, there is no subsequent effect on physiological and kinematic responses during a sub-maximal training set following a standardised warm-up.